An investigation of copper(I) active metal template synthesis of interlocked structures for anion binding - Sutton, S (2019)
This thesis describes the synthesis and study of a series of novel macrocycles containing propyl-, 1,2-hydroxymethyl benzene-, and 1,3-benzene-linked bis(iodo)triazole motifs, as well as computational investigation of these and further bis(iodo)triazole marcrocycles Chapter One introduces the field of supramolecular chemistry, highlighting areas of particular relevance to this thesis viz halogen bonding, anion coordination, recognition, and templa- tion routes to the synthesis of interlocked structural frameworks. Chapter Two describes the synthesis of a series of macrocycles, containing propyl- and 1,2- hydroxymethyl benzene-linked bis(iodo)triazole motifs. Attempts to include them into [2]rotaxanes, pursuing understanding of how macrocycle flexibility impacts active metal templation outcomes are reported. Chapter Three details computational methods used to determine if a simplified computational model has potential as a predictor for macrocycle viability in an active metal template re- action. Minimal conformations of known and novel macrocycles are generated complexed with CuI cations and the results presented for comparison with experimental outcomes. Chapter Four focuses on the study of how macrocycle size variation impacts active metal template yield. A series of novel macrocycles containing the 1,3-bis(iodo)triazole ben- zene motif were prepared, then used in active metal template reactions to generate novel [2]rotaxanes for yield comparison. Chapter Five provides a summary of the major conclusions of this thesis. Chapter Six contains procedures pertaining to chemicals, instrumentation, data handling and analytical protocols, as well as detailing synthetic methods and characterisation of novel compounds. Chapter Seven provides the references cited within Chapters One to Six.